2019
DOI: 10.3892/etm.2019.8184
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑30d‑5p promotes ovarian granulosa cell apoptosis by targeting Smad2

Abstract: Polycystic ovarian syndrome (PCOS) is one of the leading causes of female infertility. MicroRNA-30d-5p (miR-30d-5p) has been reported to be significantly increased during follicle stimulating hormone (FSH)-mediated progesterone secretion of cultured granulosa cells. However, its role in the proliferation and apoptosis of ovarian granulosa cells is unclear. The present study aimed to investigate the role of miR-30d-5p in the proliferation and apoptosis of ovarian granulosa cells. Bioinformatic analysis and dual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 35 publications
2
11
0
Order By: Relevance
“…After trans-activating by steroidogenic factor 1, miR-202-5p promotes apoptosis of goat GCs through regulating TGFβR2 (Ding et al 2020). And it finds that miR-30d-5p promotes GC apoptosis through suppressing Smad2 (Yu and Liu 2020). Likewise, our data demonstrated that inhibition of miR-128-3p repressed apoptosis in rat GCs induced by NE.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…After trans-activating by steroidogenic factor 1, miR-202-5p promotes apoptosis of goat GCs through regulating TGFβR2 (Ding et al 2020). And it finds that miR-30d-5p promotes GC apoptosis through suppressing Smad2 (Yu and Liu 2020). Likewise, our data demonstrated that inhibition of miR-128-3p repressed apoptosis in rat GCs induced by NE.…”
Section: Discussionsupporting
confidence: 55%
“…2020 ). And it finds that miR-30d-5p promotes GC apoptosis through suppressing Smad2 (Yu and Liu 2020 ). Likewise, our data demonstrated that inhibition of miR-128-3p repressed apoptosis in rat GCs induced by NE.…”
Section: Discussionmentioning
confidence: 99%
“…The decreased bioavailability of TGF-β1 is correlated with an improvement in some abnormal clinical parameters of PCOS [40]. Enhanced Smad2 level by plasmid can reduce apoptosis and improve cell viability of rat ovarian granulosa cells [41]. TGF-β1/Smad3 pathway regulates apoptosis of granulosa cells, through inhibiting ovarian follicle development of PCOS [42].…”
Section: Discussionmentioning
confidence: 96%
“…Besides, numerous studies have reported on the role of different miRNAs in GCs apoptosis in PCOS. Some miRNAs inhibit apoptosis, such as miR‐129 (Zhu et al, 2020), miR‐17‐5p (G. Liu et al, 2020), miR‐33b, and miR‐142 (Y. Li et al, 2019), whereas others promote apoptosis, including miR‐423 (Y. Li et al, 2019), miR‐30d‐5p (Yu & Liu, 2020), miR‐135a (Wei et al, 2020), and miR‐204 (X. Sun et al, 2019).…”
Section: Discussionmentioning
confidence: 99%